DNA barcoding for assessment of exotic molluscs associated with maritime ports in northern Iberia. Issue 2 (7th February 2016) - Pejovic, Ivana; Ardura, Alba; Miralles, Laura; Arias, Andres; Borrell, Yaisel J.; Garcia-Vazquez, Eva
ABSTRACT: Ports are gateways for aquatic invasions. New arrivals from maritime traffic and disturbed environmental conditions can promote the settlement of exotic species. Molluscs fall into the most prevalent group of invasive species and can have a tremendous impact on aquatic ecosystems. Here we have investigated exotic molluscs in three ports with different intensities of maritime traffic in the Cantabrian Sea. DNA barcodes were employed to identify the species using BLASTn and BOLD IDS assignment. Deep morphological analysis using diagnostic criteria confirmed BLAST species assignation based on COI and 16S rRNA genes. Results confirmed the usefulness of DNA barcoding for detecting exotic species that are visually similar to native species. Three exotic bivalves were identified: Ostrea stentina (dwarf oyster), the highly invasive Crassostrea gigas (Pacific oyster) and Xenostrobus securis (pygmy mussel). This is the first record of O. stentina in the Bay of Biscay and the second of X. securis in the Cantabrian Sea. Furthermore, we report on the presence of the cryptogenic mussel Mytilaster minimus in the central Cantabrian Sea. These exotic species might have been overlooked due to their phenotypic similarity with co-occurring oyster and mussel species. This study illustrates how combining morphological and DNA taxonomic analysis can help in port and marina biosecurity surveys.